2017
DOI: 10.17265/2328-2185/2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Using the Balanced Scorecard as a Strategic Management System in the Libyan Construction Industry

Abstract: Libya is a developing country that has a growing construction industry, however, the management of construction projects frequently experiences challenges with time and cost restraints and this affects the overall performance of the project as well as the performance of the project managers. The main aim of this paper is to apply BSC in the Libyan construction industry and evaluate the factors that impact project manager performance and their ability to complete and deliver projects successfully in Libya. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The influence of response and monitoring of risks (RMP-RMR) on Libyan construction projects' performance was formulated through hypothesis 3, and it was found that discovered that RMP-RMR also gave positive impact on the construction projects' performance with corresponding values of β = 0.210, t =3.312, p <0.001. The effect of RMP-RMR was the improvement of performance by almost 21% which agreed with the findings of the study of ( (Nguyen & Watanabe (2017), Shibani and Gherbal (2018) and Marinich ( 2020)).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The influence of response and monitoring of risks (RMP-RMR) on Libyan construction projects' performance was formulated through hypothesis 3, and it was found that discovered that RMP-RMR also gave positive impact on the construction projects' performance with corresponding values of β = 0.210, t =3.312, p <0.001. The effect of RMP-RMR was the improvement of performance by almost 21% which agreed with the findings of the study of ( (Nguyen & Watanabe (2017), Shibani and Gherbal (2018) and Marinich ( 2020)).…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion the above findings supported ( (Shibani & Gherbal (2018), Marinich, (2020 and Ekung et al, (2021)) that the RM practices (RMP-RI, RMP-RA, and RMP-RMR) had positive effects on enhancing projects performance. By adopting these practices, the performance of the studied Libyan construction companies has increased to almost 83% overall.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These objectives are based on revenue growth, cost reduction and productivity improvement. They can usually be measured by return on investment, growth in sales or income, increase in market share, and economic value added (Kaplan & Norton, 1992;Kaplan & Norton, 2007;Shibani & Gherbal, 2018). This variable will be measured in the questionnaire by the questions from (1) to (4) in the financial section.…”
Section: The Financial Perspectivementioning
confidence: 99%
“…It reflects the organization's ability to attain customer satisfaction by achieving the appropriate quality and price. This perspective includes multiple performance dimensions such as customer satisfaction, customer retention, and customer profitability (Kaplan & Norton, 1992;Kaplan & Norton, 2007;Shibani & Gherbal, 2018). This variable will be measured in the questionnaire by the questions from (1) to (4) in the customer section.…”
Section: The Customer Perspectivementioning
confidence: 99%